2008
DOI: 10.1111/j.1365-2249.2008.03601.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dendritic cell functions because of depletion of natural killer cells disrupt antigen-specific immune responses in mice: restoration of adaptive immunity in natural killer-depleted mice by antigen-pulsed dendritic cell

Abstract: SummaryThe primary aim of this study was to evaluate the role of natural killer (NK) cells on antigen-specific adaptive immune responses. After analysing the mechanism of impaired adaptive immune responses of NK-depleted mice, an immune interventional approach was developed to restore adaptive immunity in NK-depleted mice. NK cells were depleted from mice by administration of anti-asialo GM1 antibody (100 ml/mouse), twice, at an interval of 48 h. Hepatitis B surface antigen (HBsAg) was administered intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…The data confirmed and extended the previous findings on the cross-talk between NK cell and DC in models related to model Ags (18,39), parasite infections (19,20), and tumors (21). To elucidate the mechanism of how NK cells promote the development of efficient adaptive Th1 response, we have analyzed the DC phenotypic and functional characteristics after infection with C. muridarum.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The data confirmed and extended the previous findings on the cross-talk between NK cell and DC in models related to model Ags (18,39), parasite infections (19,20), and tumors (21). To elucidate the mechanism of how NK cells promote the development of efficient adaptive Th1 response, we have analyzed the DC phenotypic and functional characteristics after infection with C. muridarum.…”
Section: Discussionsupporting
confidence: 71%
“…A line of evidence indicates that NK cells can regulate DC function and that NK-DC cross-regulation plays an important role in dictating the quality and the quantity of the adaptive immune responses (16)(17)(18)(19)(20)(21). A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21).…”
mentioning
confidence: 99%
“…Investigators have shown that DCs and MFs require help from NK cells and NK cell-derived cytokines for maturation and proper functioning of APCs (39,40). A recent study has shown that DCs isolated from NK cell depleted mice could not be loaded with Ag and were incapable of activating memory specific lymphocytes (41). Cytokine production by these activated lymphocytes modulates other splenic populations, including DCs, MFs, neutrophils, and NK cells in control animals, which when might account for the significantly attenuated overall levels of IL-6 and IFN-g observed in immunized NK cell-depleted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NK cell recruitment due to activation by Ribi may be less extensive than that induced by the injection of DCs that have been activated in vitro (29). Furthermore, the interaction between DCs and NK cells can result in negative as well as positive sequelae (41)(42)(43). Clearly, however, mature NK cells are localized to the splenic red pulp (44 -46) where, upon activation, they are likely to encounter B cells in the marginal zone.…”
Section: Discussionmentioning
confidence: 99%